Basal metabolic rate shapes the development and progression of hepatocellular carcinoma - Sebastian Maciak; Diana Sawicka; Irena Kasacka; Lech Chyczewski; Halina Car; Marek Konarzewski (BMC Cancer)
Abstract Background Among several cancer risk factors, the variation in basal metabolism rate (BMR), which constitutes up to 70% of total energy expenditures in humans, may be causally linked with neoplasm development. As BMR reflects the mass of metabolically active organs, being the function of cell size and/or cell number, it may serve as a critical metabolic proxy of cancer susceptibility in the context of cell growth and cell size. Methods We examined the progression and rate of development of chemically induced hepatocellular carcinoma, using lines of mice divergently selected for high or low BMR and differing with respect to both the size of metabolically active organs and their cellular architecture. Results The high BMR mouse line developed hepatocellular carcinoma much faster and with a higher progression rate, accompanied by a considerable increase in liver size and hepatocyte enlargement, as compared to the low BMR mouse line. The HBMR mice also manifested an increased expression of metabolism- and cell size-related genes (mTOR, PI3K, c-myc, but not IGF-1), with a simultaneous decrease in the activity of tumor suppressors (p-53, APC) at the beginning of cancerogenic processes, promoting further neoplasm expansion.  Conclusion Presented results suggest that genetically determined high BMR may additionally burden liver cells via changes in the action of specific genes, leading to higher tumorigenesis.